Nord et Sud dans la construction de l’identité noire américaine : réflexions sur le Mouvement pour les Droits Civiques - Anne Stefani (Anglophonia)
The present article examines the role played by the southern Civil Rights Movement of the 1960s in the construction of a national African American identity. Through the example of the Student Nonviolent Coordinating Committee, it analyzes the Freedom Movement from a North/South perspective, showing that the Movement allowed the convergence and interaction of two specific black identities which had developed in the North and in the South in the wake of the Great Migration. After exposing the main characteristics of these two identities at mid-20th century, the article focuses on the evolution of SNCC and of a selection of its key members to demonstrate how the Movement absorbed and transformed distinctive features of black northern and southern cultures, giving birth, ultimately, to a new black identity in which North and South became united after an era of separate development.